Conditions for successful active investment in terms of the state and the far-sighted interests of the business - Jurij V. Vasilenko (Ekonomika, 2021)
For the macro characteristic of active investment, we introduced the concept of the technical productivity of investment. It characterizes an investment's capacity to reduce the norm of material or labor costs. Based on the technical productivity of investment, we derived the equation (not identity) of economic dynamics. We have proposed measuring the efficiency of investments by added-value to reflect their effectiveness for the business owner's far-sighted interests in minimizing the turnover of skilled workers. We have proposed to use the criteria in terms of the state - the maximum of the real GDP growth and the maximum of the sum of real GDP for the country as a whole. We defined the limits of an investment's technical productivity, for which the investor receives the desired payback or effectiveness, and an economy in maximal development. For this, we used our causal simulation model of Ukraine's economy dynamics, which, in contrast to the known models, reflects the main types of legal and shadow economic activities in their relationships.
Keywords: 330; technical productivity of active investment; efficiency of investment by added-value; criteria in terms of the state; limits of investment technical; productivity for successful investments; model of legal and shadow economic activities